Chloroplast genome of Aconitum barbatum var. puberulum (Ranunculaceae) derived from CCS reads using the PacBio RS platform - Chen, Xiaochen; Li, Qiushi; Li, Ying; Qian, Jun; Han, Jianping (Frontiers in Plant Science, 2015)
The chloroplast genome (cp genome) of Aconitum barbatum var. puberulum was sequenced using the third-generation sequencing platform based on the single-molecule real-time (SMRT) sequencing approach. To our knowledge, this is the first reported complete cp genome of Aconitum, and we anticipate that it will have great value for phylogenetic studies of the Ranunculaceae family. In total, 23,498 CCS reads and 20,685,462 base pairs were generated, the mean read length was 880 bp, and the longest read was 2,261 bp. Genome coverage of 100% was achieved with a mean coverage of 132× and no gaps. The accuracy of the assembled genome is 99.973%; the assembly was validated using Sanger sequencing of six selected genes from the cp genome. The complete cp genome of Aconitum barbatum var. puberulum is 156,749 bp in length, including a large single-copy region of 87,630 bp and a small single-copy region of 16,941 bp separated by two inverted repeats of 26,089 bp. The cp genome contains 130 genes, including 84 protein-coding genes, 34 tRNA genes and eight rRNA genes. Four forward, five inverted and eight tandem repeats were identified. According to the SSR analysis, the longest poly structure is a 20-T repeat. Our results presented in this paper will facilitate the phylogenetic studies and molecular authentication on Aconitum.